Analisis Tanggung Jawab Ahli Waris terhadap Utang Pewaris Berdasarkan Prinsip Pemisahan Harta Warisan dan Harta Pribadi - Rayi Kharisma Rajib; Brina Aspasia Nugraena; Mutiara Kartika Sari Damanik (PT. Hasba Edukasi Mandiri, 2026)
This study is based on the public’s limited understanding of heirs’ liability for the deceased’s debts under civil law. This article aims to analyze the nature of heirs’ liability for the deceased’s debts and the separation of the deceased’s estate from personal assets in providing legal protection. The research method employed is normative legal research, which views law as norms or principles that evolve within society, utilizing both a statutory approach and a conceptual approach. The data were derived from primary sources, specifically the Civil Code KUHPerdata, which serves as the primary legal framework detailing inheritance matters, as well as secondary sources, including scholarly literature such as books, academic journals, articles, and the perspectives of legal experts. The results of the study indicate that the forms of heirs’ liability for the decedent’s debts involve three positions: full acceptance of the inheritance, acceptance of the inheritance with conditions or limitations, and rejection of the inheritance. The principle of separation between the estate and personal assets plays a crucial role in providing legal protection by limiting the heirs’ liability to the value of the estate they have received.